2013
DOI: 10.1016/j.biortech.2013.02.076
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic co-digestion of cattle manure and food waste supplemented with crude glycerin in induced bed reactor (IBR)

Abstract: Thermophilic co-digestion of cattle manure and food waste supplemented with crude glycerin in induced bed reactor (IBR) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…Additionally, the oxidation state of the carbon content in the organic matter influences the ratio of CH 4 and CO 2 , so that the more organic carbon is reduced, the more methane will be generated (Angelidaki et al 2009). Moreover, Castrillón et al (2013) stated that the methane yield can always be improved by supplementing the cattle manure and food waste co-substrates with a small quantity of glycerol because glycerol has better degradability than cattle manure. The composition of crude glycerol determines the maximum amount of glycerol that can be added to the anaerobic digestion.…”
Section: Biogas Productionmentioning
confidence: 99%
“…Additionally, the oxidation state of the carbon content in the organic matter influences the ratio of CH 4 and CO 2 , so that the more organic carbon is reduced, the more methane will be generated (Angelidaki et al 2009). Moreover, Castrillón et al (2013) stated that the methane yield can always be improved by supplementing the cattle manure and food waste co-substrates with a small quantity of glycerol because glycerol has better degradability than cattle manure. The composition of crude glycerol determines the maximum amount of glycerol that can be added to the anaerobic digestion.…”
Section: Biogas Productionmentioning
confidence: 99%
“…1b. The higher biogas production of 0.7 L g -1 VS removed is achieved by codigesting organic kitchen waste (OKW) and cattle manure (OKW:CM mixing ratio 75:25) (Aragaw et al 2013), but also cattle manure, food waste with glycerin (87:10:3) (Castrillon et al 2013) and cattle manure, food waste, sewage sludge (70:20:10 TS concentration around %4) (Marañón et al 2012) give very high methane generation of 0.64, 0.61 L g -1 VS with 93 % COD, 53 % VS removal, respectively. In a field study, biogas yield of 0.41 and 0.47 L g -1 VS loaded is conducted by co-digesting CM, chicken manure without or with maize silage around 50 % VS reduction in mesophilic condition (Yangin-Gomec and Ozturk 2013).…”
Section: Important Parameters For Operating and Performancementioning
confidence: 99%
“…Different researchers have studied the co-digestion of manure with a wide variety of cosubstrates such as fruit and vegetable wastes (Callaghan et al, 2002), the organic fraction of municipal solid waste (Capela et al, 2008), food waste (Neves et al, 2009;Banks et al, 2011) and raw glycerin (Astals et al, 2012;Castrillón et al, 2011;Castrillón et al, 2013b). Studying the co-digestion of cattle slurries with fruit and vegetable wastes (FVW) and with chicken manure, Callaghan et al (2002), found that increasing the proportion of FVW from 20% to 50% improved the methane yield from 230 to 450 L CH 4 /kg VS. Capela et al (2008) evaluated the technical feasibility of anaerobic co-digestion with three types of organic solid waste under mesophilic conditions: the organic fraction of municipal solid waste (OFMSW), industrial sludge, and cattle manure.…”
Section: Introductionmentioning
confidence: 99%